Effects of Teaching Materials on Learning Salt Factory Topics Based on Ethnoscience to Improve Mastery of Students Concepts and Life Skills - Sarwi Sarwi; Siti Fathonah; Meutia Anis; Fahrur Rozi; Sri Wardani; Winarto Winarto (Postgraduate, University of Mataram, 2023)
Understanding concepts and life skills is important for students to develop. This study aims to analize effects of teaching materials on learning salt factory topics based on ethnoscience to improve mastery of concepts and life skills. This research is a quasi-experimental study using a non-equivalent design. Data collection techniques in this study used tests to measure concepts and questionnaires to measure life skills. The research instruments were multiple choice tests and a Likert scale questionnaire. The instrument meets the validity and reliability. The sample in this study was 77 elementary school students. Data analysis technique usedÂ paired t-tests, and one ways ANOVA. The application of ethnoscience-based thematic learning tools in experimental 1 and experiment 2 showed higher concept understanding posttest results compared to control groups with conventional learning. This was proved by the sig value. < 0.05 and the average posttest score in experiment class 1 was 80.32 and experiment 2 was 83.37 higher than the control class of 75.25. learning physics salt factory materials sourced from local wisdom can increase mastery of concepts and increase understanding of life skills. This teaching effective enough in improving the mastery of concepts and developing students' life skills.